Effect of Naa, Iba and Keradix on Rooting Potential of Rhizophora apiculata Blume Hypocotyls - Kathiresan, K.; Moorthy, P. (Indian Forester, 1994)
Effect of growth promoting substances on rooting of Rhizophora apiculata hypocotyl was studied in the intertidal areas of the Vellar estuary of Porto Novo marine environment. IBA and NAA were found promotory at lower concentrations less than 6 ppm and Keradix at higher concentration above 1 %. NAA at 2 ppm in 6 hours of treatment and Keradix at 1% in 3 hours of treatment, induced maximum rooting characteristics and the treated hypocotyls easily got adapted to the natural conditions.